القيم في مجال التربية البدنية والرياضية - حمامة, طاهري; حميد, دشري (Sciences de l'Homme et de la Société, 2017)
هدفت هذه الدراسة الى التعرف على القيم المتضمنة في منهاج التربية البدنية والرياضية للمرحلة الثانوية، وتكون مجتمع الدراسة وعينتها من المناهج التربوية للسنوات الثلاثة للمرحلة الثانوية، ولتحديد ذلك تم جمع بيانات الدراسة من خلال أداة لتحليل المحتوى صممت خصيصا لذلك من قبل الباحثين نصر محمد المقابلة، وزيد علي البشايرة، تتوفر على كل الشروط السيكوميترية ( صدق وثبات). والنتائج المستخلصة بعد تطبيق الأداة سيتم التعرف عليها في العرض التالي.       Abstract :          The purpose of this study is the identification of values in Physical Education and Sport Programs at the secondary level, the population of this study is represented by the educational programs for three years at the secondary level, the data were collected through the tool of analysis of the contents which was established especially for that, this tool is elaborated by the researchers Nasr Mohamed, Zaid Ali elbachaiir,The results obtained after the application of the tool will be recognized later.